Free Vibrtions of Timoshenko Beams on Rigid Blocks - Auciello, N.M. (Engineering Transactions, 1993)
The aim of the paper is to analyze the vibration of Timoshenko beam resting on the most arbitrary elastically flexible supports. The boundary conditions are defined by means of a 2 x 2 flexibility matrix, and the structure is discretized according to the so-called cell procedure. The Lagrangian coordinates are selected to be the vertical displacements of the end points of the rigid bars, plus the four possible displacements of the external constraints. A numerical example is worked out in which the obtained results are compared with some known results.